The Role of Google Form As An Assessment Tool in ELT: Critical Review of The Literature - Adelia, Adelia; Miftahurrahmah, Miftahurrahmah; Nurpathonah, Nurpathonah; Zaindanu, Yoan; Ihsan, Muhammad Taufik (ETDC: Indonesian Journal of Research and Educational Review, 2021)
This article aim to provide an understanding to all readers that it is necessary to know the development of assessment tool in English Language Teaching (ELT), especially in the case of using of google classroom in the current year of covid-19 pandemic. It presents the advantages of google form, the ways to upset google form and the empirical studis on google form as an assessment tool in ELT. This article is made in the form of a study of documents and literatures whose understanding of knowledge is used as an analysis. In view of this, the Indonesian teachers should be carefully designed the worksheet in google form, so it can be function to do assessment. However, it should not use completly to replace the traditional methods.